To Be or Not to Be Expressed: The First Evidence of a Nucleolar Dominance Tissue-Specificity in Brachypodium hybridum - Borowska-Zuchowska, Natalia; Robaszkiewicz, Ewa; Mykhailyk, Serhii; Wartini, Joanna; Pinski, Artur; Kovarik, Ales; Hasterok, Robert (Frontiers in Plant Science, 2021)
Nucleolar dominance (ND) is an epigenetic, developmentally regulated phenomenon that describes the selective inactivation of 35S rDNA loci derived from one progenitor of a hybrid or allopolyploid. The presence of ND was documented in an allotetraploid grass, Brachypodium hybridum (genome composition DDSS), which is a polyphyletic species that arose from crosses between two putative ancestors that resembled the modern B. distachyon (DD) and B. stacei (SS). In this work, we investigated the developmental stability of ND in B. hybridum genotype 3-7-2 and compared it with the reference genotype ABR113. We addressed the question whether the ND is established in generative tissues such as pollen mother cells (PMC). We examined condensation of rDNA chromatin by fluorescence in situ hybridization employing state-of-art confocal microscopy. The transcription of rDNA homeologs was determined by reverse-transcription cleaved amplified polymorphic sequence analysis. In ABR113, the ND was stable in all tissues analyzed (primary and adventitious root, leaf and spikes). In contrast, the 3-7-2 individuals showed a strong upregulation of the S-genome units in adventitious roots but not in other tissues. Microscopic analysis of the 3-7-2 PMCs revealed extensive decondensation of the D-genome loci and their association with the nucleolus in meiosis. As opposed, the S-genome loci were always highly condensed and localized outside the nucleolus. These results indicate that genotype-specific loss of ND in B. hybridum occurs probably after fertilization during developmental processes. This finding supports our view that B. hybridum is an attractive model to study ND in grasses.